일부 치과위생사의 대학졸업연한 차이에 따른 희망진로와 현 근무처와의 일치도 및 직업 만족도 조사 - 최용금; 김경미; 김선일; 신보미; 류다영; 정세환; 이민선 (Han'guk Ch'iwisaeng Hakhoe chi, 2011)
Objectives : Five years have passed since the departments of dental hygiene with four-year term released their graduates. It is necessary to investigate concordance between desired career and current job and job satisfaction in dental hygienists according to graduation term. Accordingly, a survey on concordance between desired career and current job and job satisfaction in dental hygienists according to graduation term was conducted to obtain a basis necessary for providing right job consciousness to students of departments of dental hygiene. Methods : Of departments of dental hygiene nationwide, a total of four departments consisting of two departments with 3-year term and two departments with 4-year term were randomly selected. Of 683 graduates for 2006-10 of the selected departments, 163 graduates who agreed to participate in this study through telephone and e-mail were chosen as subjects. The data of 159 graduates were analyzed except for 4 graduates who did not respond to job satisfaction. The questionnaire consisted of a total of 17 questions: 5 general questions such as graduation term, and current job and salary, 2 questions for desired career at the time of entrance and graduation,and 10 questions for the satisfaction of current job and working environments. Concordance between the desired career at the time of entrance and graduation and current job was calculated using Kappa-value. A cross analysis was conducted to investigate job satisfaction according to general features and graduation term. A statistical significance was examined using X^2-test (p<0.05). Results : The Kappa-value for concordance between the desired career at the time of graduation and the current job was 0.288, showing slightly low concordance. In particular, the Kappa-value was 0.089 in the graduates of departments of dental hygiene with 3-year term, which showed significantly low concordance. The job satisfaction of the graduates was 49.1%, which was higher in the graduates with 4-year term than in the graduates with 3-year term, but was statistically insignificant (p>0.05). The detailed job satisfaction was all higher in the graduates with 4-year term than in the graduates with 3-year term except for distance to a working place, but a statistical significance was only found in working place recognition and regional status (p<0.05 ). Conclusions : This study showed differences in concordance between desired career and current job and job satisfaction between the graduates of departments of dental hygiene with 3-year term and the graduates of departments of dental hygiene with 4-year term. Therefore, the curriculum of department of dental hygiene is required to be more specifically applied in accordance with graduation term. In addition, a further study is required to develop specialized curriculums in accordance with graduation term KCI Citation Count: 2